The Regeneration of Nerves and Spinal Cord About Mechanisms and Therapeutic Approaches - Klimaschewski, Lars P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2024)
This non-fiction book provides information about the latest research and therapy of nerve regeneration with catchy drawings and in a well comprehensive language. Why do nerves in the extremities regenerate, but the axons in the spinal cord do not? Can transplanted stem cells or biopolymers restore regeneration? Are bioprostheses able to functionally replace amputated arms or legs? Neuroscientist Lars Klimaschewski answers these questions and reports on exciting findings from anatomy, cell and molecular biology and neurotechnology. Find out how, among other things, a brain-computer interface processes signals from the brain to regain control over arm or leg mucles via electrodes after tetra- or paraplegia. The author Prof. Dr. med. Lars Klimaschewski is a professor at the Medical University of Innsbruck, head of the Institute of Neuroanatomy and the author of numerous papers on neuronal degeneration and regeneration. The translation was done with the help of artificial intelligence. A subsequent human revision was done primarily in terms of content.
1. Axonal regeneration in the peripheral nervous system -- 2. Axonal regeneration in the central nervous system -- 3. Saving or replacing nerve cells - which strategy is more successful? -- 3. Regeneration in the nervous system - quo vadis?
Keywords: Neurology .; Neurosciences; Biotechnology; Neurology; Neuroscience; Biotechnology